Nature-Based Solutions in Urban Landscapes: Determinants Influencing Willingness to Participate in Composting in Metropolitan Jakarta, Indonesia - Mulyana, Rachmat; Suryawan, I Wayan Koko; Ulhasanah, Nova; Septiariva, Iva Yenis; Prayogo, Wisnu; Suhardono, Sapta; Sari, Mega Mutiara; Arifianingsih, Nur Novilina; Buana, Dwinto Martri Aji (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Amidst the rapid urbanization of Jakarta, the adoption of Nature-based Solutions (NbS) like composting offers a sustainable pathway for waste management and environmental rejuvenation. This research endeavors to discern the critical factors impacting the willingness of Jakarta's metropolitan populace to participate in composting activities. The study identified key determinants through a comprehensive analysis, including the availability of composting facilities, the expertise of trained cadres, the adoption of advanced composting technologies, and routine field monitoring. Furthermore, demographic nuances, specifically marital status, and age, surfaced as influential parameters. Singles and the younger age bracket (20-29 years) exhibited distinct attitudes towards composting, hinting at underlying generational and lifestyle-based disparities. The findings provide a foundation for tailoring policies and interventions that cater to Jakarta's unique urban fabric, promoting a more inclusive and influential composting culture.